Aqueous tape casting of super-hard B4C laminates with rGO-enriched reinforcing interlayers. Issue 11 (September 2021) - Ojalvo, Cristina; Ayllón, Marcos; Ortiz, Angel L.; Moreno, Rodrigo
Highlights: Superhard materials constituted by B4 C and evenly-spaced rGO-enriched reinforcing interlayers were fabricated for the first time. The tape casting performance of B4 C suspensions and the lamination comprising GO-enriched B4 C layers have been optimized. The sintered laminates are superhard and the introduction of GO-enriched interlayers allows crack arresting. Abstract: Superhard B4 C parts with microarchitectures constituted by ceramic layers and evenly-spaced rGO-enriched reinforcing interlayers were fabricated for the first time. To this end, a concentrated slurry of B4 C with its Ti-Al sintering additive was first prepared by aqueous colloidal processing, optimizing its total solids loading and content of both binder and plasticizer to obtain, by tape casting, handleable and flexible green tapes. A semi-dilute aqueous suspension of B4 C with Ti-Al and abundant GO was also prepared to dip-coat those green tapes with a GO-enriched layer, optimizing the withdrawal rate and the dipping time. The bare and GO-coated B4 C+Ti-Al tapes were then sequentially laminated, thus yielding green multilayered laminates that finally were appropriately debinded and densified by spark plasma sintering. Vickers indentation tests demonstrated that these multilayered laminates are superhard (∼31 GPa), and that their rGO-enriched reinforcing interlayers are effective in arresting crack propagation.